Phát triển kĩ năng đọc hiểu văn bản văn học cho học sinh lớp 2 thông qua hệ thống bài tập - Lê, Phương Nga; Đỗ, Thị Lan (Tạp chí Giáo dục, 2025)
Reading comprehension skills play a crucial role in developing the competence to read and understand literary texts among second graders, one of the specific skills that needs to be focused on in the teaching of Vietnamese at the primary level. Practicing reading comprehension skills not only helps students approach, perceive, and comprehend the content of the text effectively, but also contributes to nurturing linguistic thinking, forming aesthetic emotions, and developing communication skills. Based on the analysis of theoretical issues related to literary texts, reading comprehension, reading comprehension skills and a system of practice exercises, the article proposes a system of exercises to practice reading and understanding literary texts for second graders, including three groups: (1) Exercises to practice language recognition skills; (2) Exercises to practice text meaning clarification skills; (3) Exercises to practice text response skills. The research results provide a scientific basis and practical suggestions for primary school teachers to design teaching activities that systematically and effectively develop reading comprehension skills for literary texts among second-grade students, aligning with the requirements of educational innovation.